The Effect of Excellent Service and Product Image on Customer Loyalty Through Satisfaction as an Intervening Variable at PT. Papua Regional Development Bank Sentani Branch Office - Putri Indriani; Rosnaini Daga; Nasir Hamzah (UM Purwokerto Press, 2025)
This study aims to examine the influence of service excellence and product image on customer loyalty through satisfaction as an intervening variable at PT. Bank Pembangunan Daerah Papua, Sentani Branch Office. The research was conducted at the Sentani Branch of PT. Bank Pembangunan Daerah Papua over a period of two months, from May to June 2025. The population of this study consists of customers of the Sentani Branch who have been banking with the institution for more than two years. The sample was determined using the Slovin formula, resulting in a total of 100 respondents. This research employed a survey method by distributing questionnaires to the respondents. The statistical method used to test the hypotheses was Partial Least Squares (PLS). The analysis results show that service excellence has a positive and significant effect on customer satisfaction; product image has a positive and significant effect on customer satisfaction; service excellence has a positive but not significant effect on customer loyalty; product image has a positive and significant effect on customer loyalty; customer satisfaction has a positive but not significant effect on customer loyalty; service excellence has a positive but not significant effect on customer loyalty through customer satisfaction as an intervening variable; and product image has a positive but not significant effect on customer loyalty through customer satisfaction as an intervening variable.